Rules eaudiobook - Lord, Cynthia (Recorded Books Inc., 2007)
Catherine, a 12-year-old girl with big responsibilities, loves her autistic younger brother David. But she often feels that her parents, so focused on special care for him, forget that she exists, too. Like most eight-year-old boys, David is a handful. He just doesn't know when enough is enough, and in all the commotion Catherine feels ignored. She can't help but get embarrassed by some of David's behavior—like when he throws toys in the fish tank—so she decides to start writing down rules she thinks will help him become more normal. Yet after she befriends Jason, a boy her own age who is mute and wheelchairbound, she reconsiders what it means to be normal. Rules, Cynthia Lord's Newbery and ALA Award–winning debut novel, is a tender look at the frustration, struggle, devotion, and hope experienced by families with autistic children. "... this sensitive story is about being different, feeling different, and finding acceptance."—School Library Journal